Dis-orienting mobile construction workforces: impacts and externalities within the political economy of resource-based regions. (1st October 2020) - Ryser, Laura; Halseth, Greg; Markey, Sean
ABSTRACT: The political economy of labour landscapes in resource-dependent regions continues to transform with important implications for workers, families, communities, service providers, businesses, and industries. Over time, mobile work has created a new form of worker-employer dependence where some elements of traditional local labour relationships exist, but other elements have shifted. In this paper, we focus on evolving mobile workforce practices and their associated implications for workers in the construction sector. In particular, we look at how the changing demand for mobile labour in Canada has shifted the negotiating power of both industry and workers. Within this context, we find that underdeveloped industry policies and weak senior government regulatory regimes have not kept pace with the realities of these changing mobile work landscapes. Drawing upon our case study of BC Hydro's Site C dam project in British Columbia, Canada, we situate new institutionalism within the political economy of mobile work to expand understanding of how stakeholder behaviours are affecting labour practices. Among our key findings are that industry stakeholders have failed to renew workplace policies and processes to reflect mobile labour practices. The result has been a dis-orienting environment for mobile workforces where many of the impacts or externalities associated with mobile work have been transferred to workers, their families, and their communities.